(untitled) (Training and Practice : Journal of Educational Sciences, 2017)
Life long learning is a general paradigm in the 21st century. One of the European Union’s goal is to teach effective individual learning. So giving students the opportunity to learn new learning methods and strategies is really important. I examined the learning habits of students of a primary school in a town (N=137). My first hypothesis is that there is a difference in the use of learning methods between the lower and the upper levels of primary school. However, I found significant differences in five methods, the upper level students evaluated the frequency of the use of these methods with a lower value on average. Based on this result I have concluded that the upper level students use the methods mentioned with little conscience (Ledniczki, 2016). I have also found that students who study for themselves have better grades (Table 2). This has proved my assumption – that there is a connection between effective learning and academic achievement – to be right.